Techno-economic optimization of community-based manure processing. (March 2018) - Sharara, Mahmoud A.; Runge, Troy; Larson, Rebecca; Primm, John G.
Abstract: This study investigates community-based processing of manure to produce organic fertilizer using granulation. We developed a mixed-integer optimization model to determine the minimum sale price of granulated manure, i.e., price corresponding to zero net present value (NPV = 0). We used dairy farms inventories for two regions in Wisconsin to develop case studies to evaluate community-based processing. Minimum sale price of granulated manure varied between $360 and $460 per ton based on the region and the imposed aggregation radius. Granulation facilities were located on the farm with the largest herd in each case. Selection of farms for participation in granulation facility relied on both proximity and herd size. Sensitivity analyses were performed to analyze the impacts of market changes and subsidies on the investment. Community-based manure processing was found to offer an opportunity to facilitate processing and export of nutrients due to economies of scale advantage. Graphical abstract: Unlabelled Image Highlights: Granulation can facilitate export and distribution of manure nutrients. Community-based systems reduce the total cost or processing. We present an optimization model to design community-based manure granulation. The minimum sale price of granulated manure was estimated in two case studies. Herd size and distance between farms were critical to granulation economics.